Studi Komparasi Tafsir Ayat Jabr dan Ikhtiyar dalam Tafsir Al-Zamakhshari dan Al-Razi - Fasjud Syukroni (JOURNAL OF QUR'AN AND HADITH STUDIES, 2016)
This article compares Zamakhshari’s interpretation with Rāzī’s one, regarding the verses of jabr and ikhtiyār, using a thematic method. It finds that Zamakhshari’s interpretation is deterministic and sometimes indeterministic, whereas Rāzī’s one is deterministic. Both interpretations were influenced by the contexts where the authors lived. Their interpretations reflect as thoughts which perceive the human capacity in comprehending texts as well as dealing with realities.